Pengaruh Kesehatan Bank Terhadap Pertumbuhan Laba Masa Depan Pada Perbankan (Students' Journal of Accounting and Banking, 2012)
The users of financial statements requires financial information from a company to analyze the condition and performance. The purpose of this study was to analyze the influence of the soundness of the bank with the financial ratios of earnings growth. CAR financial ratios, NPL, NIM, BOPO, and the LDR is a measure of bank health that affect the level of profit growth. Growth in corporate profits is one of the company's performance at the center of attention of investors.The population in this study are listed in the Commercial Bank of Bank Indonesia 2007-2009 period as many as 123 banks. Sample was determined by purposive sampling in order to obtain samples in accordance with the specified criteria. The sample in this study were 79 banking companies. This study analyzed using multiple linear regression analysis.Based on survey results revealed that NIM partially and BOPO significant effect on future earnings growth in corporate banking. As for the CAR, NPLs and LDR no significant effect on future earnings growth in corporate banking.Keywords: Earnings Growth, Capital Adequacy Ratio (CAR), non-performing loans (NPL), Net Interest Margin (NIM), Operating Expenses Operating Income (BOPO), and the Loan to Deposit Ratio (LDR)